Mixed Morrey spaces and their applications to partial differential equations. (March 2017) - Ragusa, Maria Alessandra; Scapellato, Andrea
Abstract: In this paper, new classes of functions are defined. These spaces generalize Morrey spaces and give a refinement of Lebesgue spaces. Some embeddings between these new classes are also proved. Finally, the authors apply these classes of functions to obtain regularity results for solutions of partial differential equations of parabolic type.